Pneumonia ANALISIS RASIONALITAS PENGGUNAAN ANTIBIOTIK DAN PENGARUHNYA TERHADAP LAMA RAWAT INAP PASIEN PNEUMONIA DI RSUD AHMAD YANI METRO, LAMPUNG: ANALYSIS OF THE RATIONALITY OF ANTIBIOTIC USE AND ITS EFFECT ON THE LENGTH OF HOSPITAL STAY IN PNEUMONIA PATIENTS AT RSUD JENDERAL AHMAD YANI METRO, LAMPUNG - Asti, Windi; Sarnianto, Prih; Sumiyati, Yati; Syahputri, Devina Harti; Suri, Nurma (JFL : Jurnal Farmasi Lampung, 2025)
Pneumonia is an acute infectious disease that affects lung tissue and is caused by bacteria, fungi, viruses, and parasites, leading to inflammation of the lung parenchyma and accumulation of inflammation in the respiratory tract. In Lampung Province, there was an increase in pneumonia case detection coverage, from 39.8% in 2020 to 40.6% in 2021. At RSUD Ahmad Yani in Metro City, Lampung, pneumonia ranks among the top 10 most common diseases. The purpose of this study was to evaluate the rationality and appropriateness of antibiotic use according to treatment guidelines in pneumonia patients. This study employed an observational descriptive-analytic design with a cross-sectional approach and data collection from patient medical records using purposive sampling. The samples consisted of inpatient records diagnosed with pneumonia infection at RSUD Ahmad Yani in Metro City during January–December 2023. Data were obtained retrospectively through medical record reviews of inpatients. Quantitative analysis of antibiotic use was conducted using the Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) method, while qualitative analysis utilized the Gyssens algorithm. Statistical calculations were performed using SPSS software with Spearman’s correlation test. In this study, from 190 antibiotic prescriptions, the ATC/DDD value was 138.18 DDD per 100 patient-days. The correlation between the rationality of antibiotic use and length of hospital stay showed a Spearman correlation coefficient of 0.42, indicating a moderate positive correlation; however, the significance value of 0.567 indicated that this relationship was not statistically significant.   Keywords : ATC/DDD, Gyssens, Length of Stay (LOS), Pneumonia, Hospital